Statistical methods in the analysis of multicentre HIV randomized controlled trials in the African region: a scoping review - Mikateko Mazinu; Nomonde Gwebushe; Samuel Manda; Tarylee Reddy (BMC Medical Research Methodology)
Abstract Background The majority of phase 3 clinical trials are implemented in multiple sites or centres, which inevitably leads to a correlation between observations from the same site or centre. This correlation must be carefully considered in both the design and the statistical analysis to ensure an accurate interpretation of the results and reduce the risk of biased results. This scoping review aims to provide a detailed statistical method used to analyze data collected from multicentre HIV randomized controlled trials in the African region. Methods This review followed the methodological framework proposed by Arksey and O’Malley. We searched four databases (PubMed, EBSCOhost, Scopus, and Web of Science) and retrieved 977 articles, 34 of which were included in the review. Results Data charting revealed that the most used statistical methods for analysing HIV endpoints in multicentre randomized controlled trials in Africa were standard survival analysis techniques (24 articles [71%]). Approximately 47% of the articles used stratified analysis methods to account for variations across different sites. Out of 34 articles reviewed, only 6 explicitly considered intra-site correlation in the analysis. Conclusions Our scoping review provides insights into the statistical methods used to analyse HIV data in multicentre randomized controlled trials in Africa and highlights the need for standardized reporting of statistical methods.